2021
DOI: 10.3346/jkms.2021.36.e58
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Effect of Probiotic Intake by the Mother on Human Breast Milk and Infant Fecal Microbiota

Abstract: Background Human breast milk (HBM) contains optimal nutrients for infant growth. Probiotics are used to prevent disease and, when taken by the mother, they may affect infant microbiome as well as HBM. However, few studies have specifically investigated the effect of probiotic intake by the mother on HBM and infant microbiota at genus/species level. Therefore, we present a comprehensive analysis of paired HBM and infant feces (IF) microbiome samples before and after probiotic intake by HBM-producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…This core bacteriome included nine genera: Staphylococcus , Streptococcus , Serratia , Pseudomonas , Corynebacterium , Ralstonia , Propionibacterium , Sphingomonas , and Bradyrhizobium [ 42 ]. However, these results were inconsistent with subsequent studies [ 43 , 48 , 49 , 50 ]. One study identified a core bacteriome of 12 genera: Staphylococcus , Streptococcus , Bifidobacterium , Balutia , Brevundimonas , Corynebacterium , Flavobacterium , Propionibacterium , Pseudomonas , Ralstonia , Rothia , and Burkholderia [ 43 ].…”
Section: The Hbm-derived Microbiomecontrasting
confidence: 82%
“…This core bacteriome included nine genera: Staphylococcus , Streptococcus , Serratia , Pseudomonas , Corynebacterium , Ralstonia , Propionibacterium , Sphingomonas , and Bradyrhizobium [ 42 ]. However, these results were inconsistent with subsequent studies [ 43 , 48 , 49 , 50 ]. One study identified a core bacteriome of 12 genera: Staphylococcus , Streptococcus , Bifidobacterium , Balutia , Brevundimonas , Corynebacterium , Flavobacterium , Propionibacterium , Pseudomonas , Ralstonia , Rothia , and Burkholderia [ 43 ].…”
Section: The Hbm-derived Microbiomecontrasting
confidence: 82%
“…Within Firmicutes , rectal swab levels for microbes from genera Fournierella and Marvinbryantia were weakly positively correlated with level of those genera in mare’s milk. Studies have found these genera in milk from humans and rats [ 31 , 32 ]. Thus, for the most part, changes within Firmicutes seemed to be better correlated with aging than with milk or lysozyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal vaginal, skin, oral, gut, uterus, and breast milk communities were reported to contribute to early life microbiota ( Collado et al, 2016 ; Ferretti et al, 2018 ; Differding and Mueller, 2020 ). Moreover, probiotics may influence the communities of breast milk and the vagina ( Liang et al, 2021 ; Shin et al, 2021 ). In this study, it was confirmed that probiotic intake could alter maternal gut microbial network and interactions.…”
Section: Discussionmentioning
confidence: 99%